STRUKTUR ORGANISASI PEMERINTAH DAERAH: SUATU ANALISIS BERDASARKAN PERATURAN PEMERINTAH NO.41 TAHUN 2007 (ANALISIS PERBANDINGAN STRUKTUR ORGANISASI PEMERINTAH DAERAH KABUPATEN BANYUMAS DENGAN KABUPATEN PURBALINGGA PROVINSI JAWA TENGAH) - Denok Kurniasih (Bina Ekonomi, 2010)
The emergence of Government Regulation No. 41 of 2007 about the organization Regional device provides a new spirit for the region to establish the organizational structure according to the needs. This regulation provides for the freedom to determine their own structure. Thus local government really can be more flexible in determining the organizational structure according to the needs of each region. However, analysis show organizational structure formed in Banyumas and Pubalingga  added even more local government  budgets.  Local government performance is not better in serving the public as users of services.  Because the existing structure instead many became major problems in the organization to the exclusion of performance. Actually Banyumas and Purbalingga has developed an organizational structure  in accordance with Regulation  No. 41 of 2007. But in translating these rules have some differences. Among them are related to the establishment of priorities, grouping and certain institutions such as agricultural extension agencies, sports agencies and community development office. In general, the issue of successful visits of the two structures is overlap each other instead of duty or have a business or a job that is not contained in the structure. This causes the existing structure has a workload that  is not evenly distributed within the organization. Besides the preparation of organizational structure  is still impressed by the political arena alone. Local governments need more innovative and creative  in exploiting opportunities discretion.  It is necessary to create organizational structure become more efficient and effective  in accordance  with regional needs and capabilities.